Kolaborasi Perguruan Tinggi dan IROPIN Tasikmalaya dalam Skrining Kesehatan Mata Masyarakat - Nurpatonah, Cucu; Milataka, Itmam; Yulianti, Ai Meri; Fitriani, Nurul Zakiatul Jannah; Purwanto, Totok; Jarnauziah, Faza Aulia; Jamil, Maretta Noorasyiah; Nursiswanti, Syifa; Rahmawati, Iis; Hidayat, Dian Taufik (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Eye health is an essential determinant of quality of life, particularly in rural communities where access to specialized medical services is often limited. This community service program was designed to provide early detection of refractive errors and cataracts through a comprehensive eye health screening conducted in Neglasari Village, Salawu District, Tasikmalaya Regency. The program involved structured coordination with the village government and IROPIN Tasikmalaya, clear task distribution among lecturers, students, and staff, followed by a series of activities including participant registration, anamnesis, refraction examinations, and cataract screening. Findings indicated that most participants presented refractive errors and presbyopia, while smaller proportions were suspected of having cataracts or other visual disorders. This program successfully enhanced community awareness, emphasizing the importance of routine examinations, sustained education, and collaborative health initiatives.